Alternative composite material for coal mining shoring systems in Norte de Santander (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2018)
Composite materials were developed using epoxy resin systems as a matrix and ceramic powder waste as reinforcement to replace the wood commonly used in shoring systems in coal mines in Norte de Santander. The characterization of the materials was carried out through bending tests and by a laboratory-level assembly of the shoring system. The optimal sizes of the caps were studied through field data collection, simulation, and design of experiments of the influencing variables. To determine the required properties of the system, reverse engineering was carried out using the Ashby methodology. The impact of deforestation due to the use of wood in the department of Norte de Santander was determined.